Development of Ispring Learning Media to Improve Student's Curiosity Character in STEM-Based Science Learning / Pengembangan Media Pembelajaran Ispring untuk Meningkatkan Karakter Rasa Ingin Tahu Siswa Pada Pembelajaran IPA Berbasis STEM - Kafa Sakinah; Retno Triwoelandari; Muhammad Fahri (Al-Mudarris: Journal Of Education, 2020)
The purpose of this study was to determine the feasibility, of ispring learning media in STEM-based science learning, to improve the character of student curiosity. This type of research is research and development Research and Development. Research and Development (R&D) with the ASSURE research model. Research instruments in the form of questionnaires and observation sheets. The results of this study obtained a percentage of the fesibility of the material aspect of 84.7% with the very valid category, the language aspect obtained by 84.2% with the very valid category, and the design aspect obtained by 75% with the valid category. So it can be concluded that the ispring learning media in STEM-based science learning to improve the character of student curiosity is feasible to use.